Penerapan Model Pembelajaran Example Non Example Untuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Dinamika Hidrosfer Kelas X SMA Negeri 10 Kota Ternate - Marthinu, Eva; Nurdin, Rusdin; hasyim, Jainudin (Universitas Khairun, 2023)
This research was conducted to improve the learning outcomes of class X students of SMA Negeri 10 Ternate City. On the subject of Hydrosphere Dynamics through the application of the Example Non Example learning model by using worksheets (questionnaires) while the data analysis techniques used are Observation, and questionnaires. To improve student learning outcomes.The type of research used is descriptive qualitative research with reference to the Example Non Example learning model. To improve student learning outcomes. The place of research is SMA Negeri 10 Kota Ternate.The completeness of student learning outcomes as a whole can be seen in cycle I as many as 33 people who have not finished or as much as 8%. Those who have not achieved mastery learning or have not reached KKM. Whereas in cycle II there was an increase in student learning outcomes as many as 32 people who completed or as many as 89% of students achieved learning mastery, so it can be said that in cycle II students can be said to have succeeded or achieved KKM